Geology, mineralogy and geochemistry of Koodakan 2 prospecting area, South of Birjand, East of Lut Block - Somayeh Samiee; Sedigheh Zirjanizadeh (Journal of Economic Geology, 2019)
Introduction The study area is located in 180 kilometers at the South of the city of Birjand and at 4 kilometers North of the Qhaleh-Zari mine, within the Central Lut Block. According to Stocklin and Nabavi (1973), the Lut Block (Eastern Iran) extends over 900 km in a north-south trend and is 200 km wide in an East-West direction. It is confined by the Nayband fault and the Tabas Block on the west, Nehbandan Fault in the east, Doruneh Fault in the north, and the Jaz- Morian Basin in the south. The sixty- five percent of the exposed rocks within the Lut Block consist of volcanic and plutonic rocks (Karimpour et al., 2011). The extensive magmatism of the area has resulted from the west-dipping subduction of the Lut Block zone (Karimpour et. al., 2005). The Koodakan area is located in the north of the Qhaleh-Zari mine, and in fact, it is comprised of the continuation of Qhaleh-Zari mineralization type. In the study area, rock units include Tertiary volcanic, intrusive, subvolcanic, and pyroclastic rocks.